THE IMPROVING STUDENTS’ READING COMPREHENSION THROUGH GRAMMAR TRANSLATION METHOD - Megawati, Megawati (English Education:Journal of English Teaching and Research, 2017)
The objective of the research is to improving students’reading comprehension throughgrammar translation method toward the tenth grade students, even semester, 2016/2017 academic year of SMK PrivateTaposDepok.This present classroom action research was mainly aimed to find out the extent of reading comprehension improved through grammar translation method. The subject of the present research were the tenth grade student of SMK Private TaposDepok in academic year 2016/2017 that consisted of 33 males and females, whereas the data collected by interview, data, and observation. The result of the post test in each cycle totally showed that there was significant improvement of the subject’ability in reading comprehension in which their it pointed out that the level improved from insufficient to good. This is evidences with the average reading test in every cycle can improved that is on cycle I=6,76; cycle II=7,35; cycle III=7,80 and the result of the interview concluded that learning reading comprehension through grammar translation method is fun for the students. This research showed positive changing behavior of the subjects in which their attitudes and motivation increased significantly toward reading comprehension. The result of the observation concluded that grammar translation method can improved students’ reading comprehension at tenth grade of SMK Private TaposDepokin Academic 2016/2017. Keywords: Reading Comprehension, Grammar Translation Method